2017
DOI: 10.17161/fec.v41i9.6841
|View full text |Cite
|
Sign up to set email alerts
|

Creating Culturally Responsive Instruction: For Students' and Teachers' Sakes

Abstract: The field of education faces a number of issues regarding how to improve the quality of school life and educational outcomes of culturally different 1 students-namely African Americans, Hispanic Americans, and American Indians. All of the issues (high dropout rates, high suspension and expulsion rates, high rates of school failure, low test scores and grades, low academic engagement, poor student-teacher relationships, etc.) fall under the umbrella of three broad areas: the achievement gap, gifted education un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 13 publications
0
22
0
4
Order By: Relevance
“…Findings indicated that when African American students were asked about their experiences with discrimination, they described hostile relationships with adults in positions of authority including teachers in school (Rosenbloom & Way, 2004 (Ford & Kea, 2009;Ford & Harris, 1996;Hollins & Guzman, 2005). Not surprising then is that African American youths report racially biased treatment within the classroom.…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%
“…Findings indicated that when African American students were asked about their experiences with discrimination, they described hostile relationships with adults in positions of authority including teachers in school (Rosenbloom & Way, 2004 (Ford & Kea, 2009;Ford & Harris, 1996;Hollins & Guzman, 2005). Not surprising then is that African American youths report racially biased treatment within the classroom.…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%
“…By using a reflective journal, scenario responses, and group and one-on-one interviews, Bennett (2012) found that the teachers demonstrated a generic understanding of culturally relevant teaching. Echoing the findings of other research, they acknowledged the need to incorporate culture by using multicultural literature or creative arts (Atwater, 2008;Ford & Kea, 2009;Goldenberg, 2014;Lawrence, 2005). One group of four students immersed themselves with students, built relationships with students, and started to critically reflect on their biases based on their dominant culture views.…”
Section: Theory To Practice For Culturally Relevant Teachersmentioning
confidence: 97%
“…Debnam et al (2015) and Ford and Kea (2009) found that students of color found academic success when taught by teachers who incorporated students' lives with the curriculum, identified which aspects of lessons matter to students, and used students' cultural capital in instructional decisions. Teachers who embrace culturally relevant teaching serve as a stimulus for improved reading achievement among students who are culturally and linguistically diverse-so much so that Debnam et al (2015) and Ford and Kea (2009) call for research into what drives a teacher to use a strengths-based approach and into the role that professional development plays in teachers' use of students' cultural capital. Accordingly, this study examines how teachers integrate culturally relevant pedagogy in implementing CCSS so that students can move toward a future in which they are contributing citizens in a democratic society.…”
Section: Research Rationalementioning
confidence: 99%
“…Ford and Kea (2009) actually prefer the term "culturally different" over "culturally diverse". Since everyone has a culture, "culturally diverse" describes every group.…”
Section: Culturally Responsive Teachingmentioning
confidence: 99%
“…Increasing the academic achievement of CLD students is possibly the most important goal of culturally relevant teaching (Howard, 2003). The focus is ensuring success and learning, whether the term culturally responsive 'teaching', 'pedagogy', or 'instruction' is used (Ford & Kea, 2009). …”
Section: Culturally Responsive Teachingmentioning
confidence: 99%